Садовська Л.М. Public administration in the sphere of civil education of Ukraine: history, development and strategic orientations - Gryshyna, Nataliia (Pressing Problems of Public Administration, 2019)
A civil education requires adhering the principles of humanization and democratization, self-regulation, multiculturalism, systematic and complex approach, interdisciplinary integration, coherence andconsistency, conformity to the culture. A process of civil education implementing is possible through the complex interaction of all the mechanisms such as logistics, institutional components and soon. Even though nowadays in Ukraine civil education development is in its heyday, but still there is potential for improvement